PERANCANGAN KUNCI PINTU RUMAH OTOMATIS MENGGUNAKAN E-KTP BERBASIS ARDUINO - Japin, Maria; Hutabri, Ellbert (LPPM Universitas Putera Batam, 2023)
Currently, cases of theft are still relatively high, because of this, tools or door locks with a more sophisticated security system are needed, such as the use of an e-KTP system. The door of the house is the main access to enter the house, but the security system at home used today is still relatively common and very vulnerable to theft or robbery. It is also very dangerous for the life of the home owner in the event of theft. So it takes a high level of security system to open or enter the door of the house. A system that can be implemented to improve security is one of them is a microcontroller-based electronic circuit system, this system makes it possible to design a home entrance security system with RFID to read e-KTP codes and manual passwords based on Arduino Mega 2560 and Arduino Nano. This system is designed with ±5V DC power supply, LCD, RFID, LED and ±12V DC solenoids. Arduino Mega 2560 and Arduino Nano as microcontrollers and solenoids and LCD as their outputs. Based on the test results, it can be concluded that the designed door security system works well and works optimally. With the help of a system that is made to open the door of the house automatically with RFID which reads the ID contained in the registered e-KTP or password, so as to minimize the occurrence of crime, especially cases of theft and burglary at the door of the house.